Relationship Between Self-Confidence and Concentration with the Smashing Ability of 12-17 Year Volleyball Athletes at the Pervas Club - Indah Zunita; Christina Fajar Sriwahyuniati; Tomoliyus; Endang Rini Sukamti (Indonesian Journal of Sport Management, 2025)
Background: The lack of systematic exploration of the contribution of mental factors to the technical performance of young athletes, especially in the execution of smashes that require precision, power, and focus. Purpose: This study aims to determine (1) identifying the relationship between self-confidence and smash ability, (2) the relationship between concentration and smash ability, and (3) the combined relationship between self-confidence and concentration on smash ability. Methods: Describe the methods used in the study. Write down the purpose of the research conducted. Methods: Describe the methods used in the study. Results: The results of the study indicate that: (1) There is a significant relationship between self-confidence and smash ability in 12-17 year old volleyball athletes at the Pervas club, with a t-value of 2.639 > t-table 2.017, sig. 0.012 and an effective contribution of 14.14%. (2) There is a significant relationship between concentration and smash ability in 12-17 year old volleyball athletes at the Pervas club, with a t-value of 2.080 > t-table 2.017, sig. 0.044 and an effective contribution of 9.36%. (3) There is a significant relationship between self-confidence and concentration with smash ability in 12-17 year old volleyball athletes at the Pervas club, with F count 6.615 > F table (2;43) 3.21 and sig. 0.003 and an effective contribution of 23.50%. Conclusion: There is a significant relationship between self-confidence and smash ability. There is a significant relationship between concentration and smash ability. There is a significant relationship between self-confidence and concentration and smash ability.